2013
DOI: 10.1097/ajp.0b013e31827a72d2
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A in Postherpetic Neuralgia

Abstract: Data confirm that BTX-A is effective and well tolerated in the treatment of PHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 15 publications
2
48
0
10
Order By: Relevance
“…Therefore, it was difficult to determine the exact onset and duration of the effects of BTX‐A in patients with SCI‐associated neuropathic pain. Previous reports on BTX‐A injections for neuropathic pain have indicated that the onset of relief and duration of effectiveness were approximately 1 to 2 weeks and 3 to 6 months, respectively 9, 10, 11, 25. Our study showed that the effective duration was at least 8 weeks.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, it was difficult to determine the exact onset and duration of the effects of BTX‐A in patients with SCI‐associated neuropathic pain. Previous reports on BTX‐A injections for neuropathic pain have indicated that the onset of relief and duration of effectiveness were approximately 1 to 2 weeks and 3 to 6 months, respectively 9, 10, 11, 25. Our study showed that the effective duration was at least 8 weeks.…”
Section: Discussionsupporting
confidence: 63%
“…However, recent studies have reported that BTX‐A for the treatment of neuropathic pain can be administered subcutaneously or intradermally 9, 10, 11, 25, 26. The effects on pain may be mediated through direct effects on the sensory system 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Em indivíduos imunocomprometidos, embora possa apresentar-se inicialmente da forma habitual, o rash tende a ser mais grave e de duração prolongada, podendo se estender a grandes áreas. 2 A neuralgia pós-herpética (NPH), principal complicação do herpes-zóster, 3,4,5 consiste na persistência da dor por período superior a quatro meses após o início do desenvolvimento do rash cutâneo e ocorre em cerca de 10% dos pacientes. 1 Tem sua incidência aumentada em pacientes com idade avançada 1,2,4 na localização oftálmica da lesão de herpes-zóster.…”
Section: Introductionunclassified
“…O quadro pode evoluir para dor crônica, muitas vezes debilitante, havendo inclusive relatos de tentativas de suicídio em casos mais graves. 2,3,4 O mecanismo fisiopatológico da neuralgia envolve os neurônios aferentes (nociceptores), terminações nervosas especializadas que respondem a estímulos (térmicos, químicos ou mecânicos) de produção de dor. Através das fibras curtas (fibras C e A-∂), os nociceptores ativados são capazes de traduzir o estímulo recebido em estímulo elétrico e transmiti-lo do sistema nervoso periférico para o sistema nervoso central (SNC), onde será interpretado no córtex como dor.…”
Section: Introductionunclassified